Modeling Growth and Yield of Schizolobium amazonicum under Different Spacings - Gilson Fernandes da Silva; Salvador Alejandro Gezan; Carlos Pedro Boechat Soares; Luciano Zumerle Zaneti (International Journal of Forestry Research)
This study aimed to present an approach to model the growth and yield of the species Schizolobium amazonicum (Paricá) based on a study of different spacings located in Pará, Brazil. Whole-stand models were employed, and two modeling strategies (Strategies A and B) were tested. Moreover, the following three scenarios were evaluated to assess the accuracy of the model in estimating total and commercial volumes at five years of age: complete absence of data (S1); available information about the variables basal area, site index, dominant height, and number of trees at two years of age (S2); and this information available at five years of age (S3). The results indicated that the 3 × 2 spacing has a higher mortality rate than normal, and, in general, greater spacing corresponds to larger diameter and average height and smaller basal area and volume per hectare. In estimating the total and commercial volumes for the three scenarios tested, Strategy B seems to be the most appropriate method to estimate the growth and yield of Paricá plantations in the study region, particularly because Strategy A showed a significant bias in its estimates.